1991
DOI: 10.1152/ajpcell.1991.260.2.c201
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic factor inhibits ciliary motility in cultured rabbit tracheal epithelium

Abstract: To study the effect of atrial natriuretic factor (ANF) on airway ciliary motility, we measured ciliary beat frequency by a photoelectric method in response to ANF in cultured tracheal epithelial cells from rabbits. Addition of ANF but not [Tyr8]ANF-(5-27) decreased ciliary beat frequency in a dose-dependent fashion; the maximal decrease from the baseline value was 24.1 +/- 1.5% (+/- SE, P less than 0.001), and a half-maximal inhibitory concentration (IC50) was 3 x 10(-12) M. Inhibition of neutral endopeptidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…These substances including phosphorylation, cytoplasmic calcium, production of prostaglandins, nitric oxide and cGMP play an important role in ciliary beating. [83][84][85] Concurrent use of drugs such as non-steroidal anti-inflammatory drug (NSAID) drugs may have some effect on the mucociliary clearance through their inhibiting effect on the enzyme cyclooxygenase that regulates the arachidonic acid metabolism. Table 5 list up a formulation factors that affect the ciliary function, Table 6 a number of drugs and Table 7 a number of excipients.…”
Section: Drugs and Formulationsmentioning
confidence: 99%
“…These substances including phosphorylation, cytoplasmic calcium, production of prostaglandins, nitric oxide and cGMP play an important role in ciliary beating. [83][84][85] Concurrent use of drugs such as non-steroidal anti-inflammatory drug (NSAID) drugs may have some effect on the mucociliary clearance through their inhibiting effect on the enzyme cyclooxygenase that regulates the arachidonic acid metabolism. Table 5 list up a formulation factors that affect the ciliary function, Table 6 a number of drugs and Table 7 a number of excipients.…”
Section: Drugs and Formulationsmentioning
confidence: 99%
“…Human BNP 32 has been shown to be biologically active in other mammalian models (Takagi & Araki, 1992). The concentrations of natriuretic peptides required to elevate cyclic GMP (10 −5 m) were 10 and 10 fold greater than have previously been shown to be active in human cultured nasal epithelial cells (Geary et al , 1993) and rabbit tracheal epithelial cells (Tamaoki et al , 1991), respectively. Our results suggest that GC M is present in much smaller quantities than GC s in ovine tracheal epithelial cells.…”
Section: Discussionmentioning
confidence: 75%
“…Functional ANP receptors have previously been demonstrated by ultra‐cytochemical localization on rat bronchiolar epithelium (Rambotti & Sprecca, 1991). Tamaoki et al (1991) found that ANP increases cyclic GMP levels (approximately 2–3 fold increase) in rabbit cultured tracheal epithelial cells, but did not investigate the effect of other natriuretic peptides or NO donors. In human cultured nasal epithelial cells Geary et al (1993) found elevations in cellular cyclic GMP (approximately 30 fold increase) levels in response to SNP and CNP, but not ANP, BNP or STa toxin.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations